Hypoxia Can Induce Migration of Glioblastoma Cells Through a Methylation-Dependent Control of ODZ1 Gene Expression - Carlos Velásquez; Carlos Velásquez; Sheila Mansouri; Olga Gutiérrez; Yasin Mamatjan; Pilar Mollinedo; Shirin Karimi; Olivia Singh; Nuria Terán; Juan Martino; Gelareh Zadeh; Gelareh Zadeh; et al. (Frontiers in Oncology, 2019)
The transmembrane protein ODZ1 has been associated with the invasive capacity of glioblastoma (GBM) cells through upregulation of RhoA/ROCK signaling, but the mechanisms triggering the ODZ1 pathway remain elusive. In addition, it is widely accepted that hypoxia is one of the main biological hallmarks of the GBM microenvironment and it is associated with treatment resistance and poor prognosis. Here we show that hypoxic tumor regions express higher levels of ODZ1 and that hypoxia induces ODZ1 expression in GBM cells by regulating the methylation status of the ODZ1 promoter. Hypoxia-induced upregulation of ODZ1 correlates with higher migration capacity of GBM cells that is drastically reduced by knocking down ODZ1. In vitro methylation of the promoter decreases its transactivation activity and we found a functionally active CpG site at the 3'end of the promoter. This site is hypermethylated in somatic neural cells and mainly hypomethylated in GBM cells. Mutagenesis of this CpG site reduces the promoter activity in response to hypoxia. Overall, we identify hypoxia as the first extracellular activator of ODZ1 expression and describe that hypoxia controls the levels of this migration-inducer, at least in part, by regulating the methylation status of the ODZ1 gene promoter.